Knowledge work intensification and self-management: the autonomy paradox. (1st December 2016) - Oscar Pérez-Zapata; Amparo Serrano Pascual; Gloria Álvarez-Hernández; Cecilia Castaño Collado
Abstract : In the analysis of the sustainability of knowledge work environments, the intensification of work has emerged as probably the single most important contradiction. We argue that the process of knowledge work intensification is increasingly self-driven and influenced by subjectification processes in the context of trends of individualisation and self-management. We use a qualitative case study of a leading multinational company in the information and communications technology sector (considered to be 'best-in-class') to discuss this intensification and its linkage with self-disciplining mechanisms. The workers studied seem to enjoy a number of resources that current psychosocial risk models identify as health promoting (e.g. autonomy, learning, career development and other material and symbolic rewards). We discuss the validity of these models to assess the increasingly boundaryless and self-managed knowledge work contexts characterised by internalisation of demands and resources and paradoxical feelings of autonomy. Knowledge work intensification increases health and social vulnerabilities directly and through two-way interactions with, first, the autonomy paradox and new modes of subjection at the workplace; second, atomisation and lack of social support; third, permanent accountability and insecurity; and finally, newer difficulties in setting boundaries.